STRENGTHENING STUDENTS’ CHARACTER THROUGH ISLAMIC RELIGIOUS EDUCATION BASED ON THE PROFILE OF PANCASILA STUDENTS IN THE INDEPENDENT CURRICULUM - Wicaksono, Muhammad Eko Arief (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This  research  explores  and  analyzes  the  role  of  Islamic  Religious  Education learning  in  forming  student  character  at  the  Siti  Chodijah  Islamic  Elementary School,  Probolinggo.  Islamic  religious  education  is  vital  in  shaping  student character, especially at the elementary level in Islamic schools. This research uses a qualitative approach with a case study method to explore students' experiences and perceptions of Islamic Religious Education learning at Siti Chodijah Islamic Elementary  School.  Data  was  collected  through  observation,  interviews,  and document  analysis.  The  research  results  show  that  learning  Islamic  Religious Education  at  Siti  Chodijah  Islamic  Elementary  School  significantly  shapes student character. A learning process that integrates Islamic values, ethics, and morality  can  positively  impact  students'  character  development.  The  Islamic Religious Education teacher at this elementary school plays the leading role as a facilitator of character  formation by  teaching  the  values  of  faith,  noble morals, and  Islamic  social  attitudes.  Apart  from  that,  a  school  environment  based  on Islamic  values  also  shapes  student  character.  Collaboration  between  schools, teachers,  and  parents  is  the  key  to  creating  an  educational  environment supporting  character  formation.  These  findings  can  be  a  reference  for  Islamic schools and related parties to continue improving the quality of Islamic Religious Education  learning  to  shape  students'  character  with  integrity  and competitiveness in society.